Mutational landscape of normal epithelial cells in Lynch Syndrome patients - Lee, Bernard C. H.; Robinson, Philip S.; Coorens, Tim H. H.; Yan, Helen H. N.; Olafsson, Sigurgeir; Lee-Six, Henry; Sanders, Mathijs A.; Siu, Hoi Cheong; Hewinson, James; Yue, Sarah S. K.; Tsui, Wai Yin; Chan, Annie S. Y.; et al. (Nature communications, 2022)
Lynch Syndrome (LS) is an autosomal dominant disease conferring a high risk of colorectal cancer due to germline heterozygous mutations in a DNA mismatch repair (MMR) gene. Although cancers in LS patients show elevated somatic mutation burdens, information on mutation rates in normal tissues and understanding of the trajectory from normal to cancer cell is limited. Here we whole genome sequence 152 crypts from normal and neoplastic epithelial tissues from 10 LS patients. In normal tissues the repertoire of mutational processes and mutation rates is similar to that found in wild type individuals. A morphologically normal colonic crypt with an increased mutation burden and MMR deficiency-associated mutational signatures is identified, which may represent a very early stage of LS pathogenesis. Phylogenetic trees of tumour crypts indicate that the most recent ancestor cell of each tumour is already MMR deficient and has experienced multiple cycles of clonal evolution. This study demonstrates the genomic stability of epithelial cells with heterozygous germline MMR gene mutations and highlights important differences in the pathogenesis of LS from other colorectal cancer predisposition syndromes. It is unclear whether somatic mutation rates are elevated in Lynch Syndrome (LS), which is the most common cause of hereditary colorectal cancer. Here, the authors use whole-genome sequencing and organoid cultures to show that normal tissues in LS patients are genomically stable, while ancestor cells of neoplastic tissues undergo multiple cycles of clonal evolution.